WAYS OF FORMATION OF COGNITIVE ACTIVITY OF JUNIOR SCHOOLCHILDREN IN UKRAINIAN LANGUAGE LESSONS - Romanyuk, S. Z. (Pedagogy of Higher and Secondary Education, 2010)
A problem of forming of cognitive sphere of personality on all of the stages of development of the system of education was one of aktualnishikh, as through an educational process realization of it was provided primary objective providing of comprehensive development of students. Realization of principle of activity in studies has an outstanding value, as an improvement of an educational - educate process depends on him. It appropriately, as studies, especially developing conducts in the system of creative development of personality, forming of individual style of activity, prospects of mental development and cognitive possibilities.